The Use of Generative Artificial Intelligence in Graduate Studies Research: A Case Study - Almoharraq, Turki Mohammed Habkoor (Arab Journal for Sciences and Research Publishing, 2024)
The study aimed to explore the level of use of King Abdulaziz University's graduate students of AI in scientific research through the application of the mixed curriculum with serial interpretation design. The study sample included King Abdulaziz University graduate students, where the researcher began using the survey descriptive curriculum based on the questionnaire as a quantitative tool. (317) Students and graduate students at King Abdulaziz University, and to achieve the study's objective in understanding the perceptions of King Abdulaziz University graduate students on the use of obstetric artificial intelligence in postgraduate research, The Zawahiri curriculum was used and a semi-codified interview tool was prepared to interview the participants, who numbered 5 graduate students at King Abdulaziz University and their selection was in the style of the maximum diversity of the University's five different colleges, The results revealed that the level of use of King Abdulaziz University's graduate students in postgraduate research (high), and the results also showed that postgraduate students have limited awareness of AI and its use in scientific research, and recommended that efforts be intensified to enhance postgraduate students' awareness of the potential and benefits of obstetric artificial intelligence in scientific research.
Keywords: obstetric artificial intelligence; postgraduate; scientific research; King Abdulaziz University